PENGEMBANGAN SISTEM INFORMASI CAGAR BUDAYA (SITARI) SEBAGAI UPAYA PELESTARIAN BUDAYA DI PROVINSI RIAU - Dewi, Meilany; Novayani, Wenda; Rachmawati, Heni; Hidayat, Erzi; Zain, Muhammad Mahrus (Jurnal Komputer Terapan, 2025)
Awareness of the importance of cultural preservation should be a fundamental concern for every Indonesian citizen, particularly in the face of the rapid cultural influences brought about by globalization and advancements in internet technology. This is especially relevant for the people of Riau Province, which is rich in historical heritage and cultural diversity. The development of SITARI (Sistem Informasi Cagar Budaya Riau) represents a strategic initiative aimed at preserving the cultural assets of Riau Province through the facilitation of cultural heritage reporting, heritage data collection, and 360-degree virtual tours.During the development process, a Focus Group Discussion (FGD) was conducted involving representatives from relevant government agencies across the 12 regencies and municipalities in Riau Province. The objective was to identify existing challenges and gather input regarding system development needs. In parallel, a public survey was carried out to capture community perspectives on the difficulties faced in reporting suspected cultural heritage objects. The system was developed using the waterfall model approach. Evaluation results indicate that the SITARI application operates effectively and performs optimally without errors. It is deemed relevant in supporting cultural literacy, heritage preservation, and the promotion of tourism in Riau. The user interface and layout received positive feedback, indicating potential for further development. Notably, the 360-degree Virtual Tour feature was highly appreciated. The application also adheres to OWASP security standards, with minor low-risk vulnerabilities identified for future improvement.